2006
DOI: 10.1128/iai.00813-06
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Peptide-Mediated Inhibition of Porphyromonas gingivalis Biofilm Formation

Abstract: Porphyromonas gingivalis is a periodontal pathogen whose primary niche is the anaerobic environment of subgingival dental plaque, but initial colonization of the oral cavity is likely to occur on supragingival surfaces that already support robust biofilm communities. Our studies have shown that P. gingivalis adheres to Streptococcus gordonii through interaction of the minor fimbrial antigen Mfa1 with a specific region of the streptococcal SspB polypeptide (residues 1167 to 1193) designated BAR. We show that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 29 publications
6
116
0
Order By: Relevance
“…As shown in Figure 4, the IC 50 for free BAR peptide was approximately 1.3 µM, consistent with the value originally reported by Daep et al 11 In contrast, the IC 50 for inhibition of adherence by BAR-modified NPs was approximately 0.2 µM, which is 6.5-fold lower than the free BAR peptide. This result indicates that BAR-modified NPs are a significantly more potent inhibitor of P. gingivalis adherence to streptococci and subsequent biofilm formation than free peptide.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…As shown in Figure 4, the IC 50 for free BAR peptide was approximately 1.3 µM, consistent with the value originally reported by Daep et al 11 In contrast, the IC 50 for inhibition of adherence by BAR-modified NPs was approximately 0.2 µM, which is 6.5-fold lower than the free BAR peptide. This result indicates that BAR-modified NPs are a significantly more potent inhibitor of P. gingivalis adherence to streptococci and subsequent biofilm formation than free peptide.…”
supporting
confidence: 78%
“…gordonii biofilms (50% inhibitory concentration [IC 50 ] =1.3 µM). 11,12 BAR also significantly reduced P. gingivalis virulence in a mouse model of periodontitis. [11][12][13] These results suggest that BAR may represent a novel therapeutic to limit P. gingivalis colonization of the oral cavity.…”
mentioning
confidence: 96%
“…Therefore, it is not clear what ligand(s), if any, SspC and SspD bind. However, the 27-amino-acid region of SspB that has been shown to mediate binding of S. gordonii to P. gingivalis is conserved in SspC (18 identical residues and five similar residues), including perfect identity of the critical NITVK subsequence (21). This observation suggests that SspC may also adhere to P. gingivalis.…”
Section: Vol 189 2007mentioning
confidence: 76%
“…Interestingly, all eight strains of Streptococcus gordonii were isolated from periodontitis patients, but the difference between the two groups was not significant (P .0.003). Lamont et al (2002) and Daep et al (2006) demonstrated that S. gordonii plays a role in colonization with Porphyromonas gingivalis, whilst Haffajee et al (2006) found this species to be more prevalent in healthy subgingival sites. Further studies are needed to clarify the possible relationship between S. gordonii and periodontal status.…”
Section: Resultsmentioning
confidence: 99%